Dinamika Kepemimpinan dan Sistem Kompensasi dalam Mendukung Kinerja Karyawan: Studi Kasus Restoran Baba Kopitiam - Muhammad Fakhri Hanif; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to analyze the dynamics of leadership and compensation systems in supporting employee performance at Baba Kopitiam Restaurant, Gajahmungkur, Semarang. The problem is focused on how leadership practices and compensation systems are implemented in daily operational activities and how these aspects are perceived by employees in relation to their work performance. To address this issue, the study is grounded in leadership theory, human resource management theory, and compensation equity theory. Data were collected through in-depth interviews, non-participant observation, and documentation involving the owner or manager, supervisors, and operational employees, and were analyzed qualitatively using an interactive analysis model. The results indicate that direct and participative leadership, with active managerial involvement in daily operations, fosters open communication, clarifies work instructions, and enhances employee discipline and teamwork. A simple yet consistent compensation system contributes to maintaining employee trust, althou gh perceptions of fairness are influenced by variations in workload under certain conditions. This study concludes that sustainable employee performance is determined not only by the level of compensation but also by leadership quality and management’s ability to adapt human resource policies to the dynamic operational conditions of the restaurant.